Integracija i vizualna prezentacija ulomaka monumentalnog metričkog natpisa iz Varaždinskih Toplica - Kuntić-Makvić, Bruna; Rendić-Miočević, Ante; Šegvić, Marina Krajcar, Igor (2011)
Systematic archaeological excavations in Varaždinske Toplice (ancient centre of the Jasi tribe, called Aquae Iasae in Roman times), conducted from the mid-20th c. by the Archaeological Museum in Zagreb, lately in cooperation with the local County museum, have revealed the remains of an architectural complex consisting of square with temples of the Capitoline triad, admirably constructed source of healing water, and baths that were transformed into an object with Christian character during the later Roman Empire. The inscriptions supplement the notion of the functioning of the Roman healing centre, the spirit of recuperation that prevailed in the Toplice, as well as the education and intellectual level of both the personnel and beneficiaries of the healing complex. The analysis has shown that the fragments of the monumental metrical inscription (A1, A2, A3, B1 and B2 ; C and D), today kept in the depository of the County museum in Varaždinske Toplice (Fig. 5), are parts of at least three different sequences. At this moment it is not possible to precisely arrange the fragments A3, C and D. The assistance afforded by computer reading analysis and textual interpretation was immense. The fragments of the inscription are too large to be moved, and they are not completely cleaned from the tuff ediments. Only with computer analysis and visual joining of fragments A1 and A2 was the metric character of the inscription confirmed, while only with computer assisted joining of the fragments B1 and B2 was it possible to recognize a meaningful and complete text, as well as to determine the precise meter. The inscriptions on the fragments A1-2 and B1-2 were inscribed in lines that conform with the verses of two metrical schemes, the dactylic hexameter (most often used in epic poetry) and iambic (most often used by lyric poets). A regular succession of long and short syllables is also recognized on the fragments A3 and C. The fragment D is too small to provide any information. The inscriptions belong to the 4th c. They were created in order to be built or slot into (or to be attached in some other way) a wall of some important public structure in the Jasae baths. The inscriptions were an important part of the environment that led to the holiest part of the complex. Goodwill of the higher power that performs the healing in the Jasae baths was invoked in these inscriptions, whether of pagan or Christian character, and we have to assume that average visitors to the Aquae Jasae baths were familiar with their contents.
Projekt MZOS
HRV